STRATEGIC ROLE OF HUMAN CAPITAL DEVELOPMENT IN ACHIEVING ORGANIZATIONAL SUSTAINABILITY: EVIDENCE FROM UNIVERSITIES IN PALEMBANG - Irayani; Frecilia Nanda Melvani; Mariyam Zanariah; Suharty; Acika Sabilillah (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
The sustainability of higher education institutions depends largely on their ability to develop and manage human capital effectively. This study examines the role of human capital development in supporting organizational sustainability at universities in Palembang. A qualitative case-study approach was employed to explore human capital practices in depth. Data were collected through semi-structured interviews, direct observations, and document reviews involving university leaders, human resource personnel, and academic staff. The data were analyzed using thematic analysis to identify key patterns and insights. The findings reveal that human capital development contributes significantly to organizational sustainability through structured training programs, knowledge-sharing activities, and continuous competency enhancement. These initiatives help universities adapt to environmental changes, foster innovation, and strengthen organizational resilience. Furthermore, the alignment of human resource development strategies with institutional goals was identified as a critical factor in achieving sustainable outcomes. This study highlights the strategic importance of human capital in sustaining higher education institutions and provides practical insights for university management in designing effective and sustainable human resource development strategies.